Curcumin Extract for Prevention of Type 2 Diabetes - Chuengsamarn, Somlak; Rattanamongkolgul, Suthee; Luechapudiporn, Rataya; Phisalaphong, Chada; Jirawatnotai, Siwanon (Diabetes care, 2012)
To assess the efficacy of curcumin in delaying development of type 2 diabetes mellitus (T2DM) in the prediabetic population. This randomized, double-blinded, placebo- controlled trial included subjects (n = 240) with criteria of prediabetes. All subjects were randomly assigned to receive either curcumin or placebo capsules for 9 months. To assess the T2DM progression after curcumin treatments and to determine the number of subjects progressing to T2DM, changes in β-cell functions (homeostasis model assessment [HOMA]-β, C-peptide, and proinsulin/insulin), insulin resistance (HOMA-IR), anti-inflammatory cytokine (adiponectin), and other parameters were monitored at the baseline and at 3-, 6-, and 9-month visits during the course of intervention. After 9 months of treatment, 16.4% of subjects in the placebo group were diagnosed with T2DM, whereas none were diagnosed with T2DM in the curcumin-treated group. In addition, the curcumin-treated group showed a better overall function of β-cells, with higher HOMA-β (61.58 vs. 48.72; P < 0.01) and lower C-peptide (1.7 vs. 2.17; P < 0.05). The curcumin-treated group showed a lower level of HOMA-IR (3.22 vs. 4.04; P < 0.001) and higher adiponectin (22.46 vs. 18.45; P < 0.05) when compared with the placebo group. A 9-month curcumin intervention in a prediabetic population significantly lowered the number of prediabetic individuals who eventually developed T2DM. In addition, the curcumin treatment appeared to improve overall function of β-cells, with very minor adverse effects. Therefore, this study demonstrated that the curcumin intervention in a prediabetic population may be beneficial.